Preparation of peanut candy with golden flaxseed - Jany de Moura Crisóstomo; Lays Arnaud Rosal Lopes Rodrigues; Ana Caroline de Carvalho Albuquerque Santos; Rosana Rodrigues de Sousa; Layanne Cristina de Carvalho Lavôr; Karoline de Macêdo Gonçalves Frota (Universidade do Estado do Rio de Janeiro, 2020)
Introduction: Golden flaxseed has important amounts of α-linolenic acid, soluble fibers and lignans, which can bring benefits to health. Objective: To prepare peanut candy added with golden flaxseed flour (GFF) in different proportions and determine its proximate composition and sensory acceptance. Materials and methods: Peanut candies were prepared with the addition of 10%, 15% and 20% of GFF. The proximate composition was determined and then acceptance tests (hedonic scale) were applied. Data were analyzed using the Kruskal Wallis test and ANOVA, adopting a significance level of 5%. Result: Regular peanut candy and a preparation added with GFF showed no difference in moisture (17.1 to 18.5%) and lipid (30.8 to 34.2%) content. As for ash content, only formulations with 15 and 20% of GFF had the highest percentage, 1.94% and 2.03%, respectively. The protein content was significantly lower (15.4 to 18.5%) and the amount of dietary fiber increased in formulations with GFF. In relation to sensory analysis, the candies added with GFF obtained good acceptability, with no significant differences regarding the attributes evaluated in comparison with the regular peanut candy. Conclusion: The data obtained allowed us to see that it is possible to partially replace peanuts with golden flaxseed flour in the preparation of candies, as the new products presented sensory characteristics that pleased consumers in all the evaluated attributes, in addition to superior nutritional value with regard to increased fiber and mineral content.